Magnetic nanoparticles for smart electrochemical immunoassays: a review on recent developments - Pastucha, Matěj; Farka, Zdeněk; Lacina, Karel; Mikušová, Zuzana; Skládal, Petr (Mikrochimica acta, 2019)
This review (with 129 refs) summarizes the progress in electrochemical immunoassays combined with magnetic particles that was made in the past 5 years. The specifity of antibodies linked to electrochemical transduction (by amperometry, voltammetry, impedimetry or electrochemiluminescence) gains further attractive features by introducing magnetic nanoparticles (MNPs). This enables fairly easy preconcentration of analytes, minimizes matrix effects, and introduces an appropriate label. Following an introduction into the fundamentals of electrochemical immunoassays and on nanomaterials for respective uses, a large chapter addresses method for magnetic capture and preconcentration of analytes. A next chapter discusses commonly used labels such as dots, enzymes, metal and metal oxide nanoparticles and combined clusters. The large field of hybrid nanomaterials for use in such immunoassays is discussed next, with a focus on MNPs composites with various kinds of graphene variants, polydopamine, noble metal nanoparticles or nanotubes. Typical applications address clinical markers (mainly blood and urine parameters), diagnosis of cancer (markers and cells), detection of pathogens (with subsections on viruses and bacteria), and environmental and food contaminants as toxic agents and pesticides. A concluding section summarizes the present status, current challenges, and highlights future trends. Graphical abstract Magnetic nanoparticles (MNP) with antibodies (Ab) capture and preconcentrate analyte from sample (a) and afterwards become magnetically (b) or immunospecifically (c) bound at an electrode. Signal either increases due to the presence of alabel (b) or decreases as the redox probe is blocked (c).
Keywords: Nanoparticles; Animals; Immunoassay; magnety; Humans; lidé; zvířata; imunoanalýza; Magnets; Electrochemistry; nanočástice; elektrochemie